2013
DOI: 10.1371/journal.pone.0053259
|View full text |Cite
|
Sign up to set email alerts
|

Phg1/TM9 Proteins Control Intracellular Killing of Bacteria by Determining Cellular Levels of the Kil1 Sulfotransferase in Dictyostelium

Abstract: Dictyostelium discoideum has largely been used to study phagocytosis and intracellular killing of bacteria. Previous studies have shown that Phg1A, Kil1 and Kil2 proteins are necessary for efficient intracellular killing of Klebsiella bacteria. Here we show that in phg1a KO cells, cellular levels of lysosomal glycosidases and lysozyme are decreased, and lysosomal pH is increased. Surprisingly, overexpression of Kil1 restores efficient killing in phg1a KO cells without correcting these lysosomal anomalies. Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
(40 reference statements)
2
25
0
Order By: Relevance
“…Glycosidase activity, phagosomal pH and proteolysis activity, and phagosomes purification Glycosidase activities in cell pellets and extracellular fluid were assessed as previously described (Froquet et al, 2008;Le Coadic et al, 2013). For phagosomal pH measurement, 3-µm carboxylated silica beads coupled to the pH-sensitive fluorophore FITC and to the pH-insensitive fluorophore Alexa-Fluor-594 were used.…”
Section: Plasmids Cell Transfections and Knockout Strainsmentioning
confidence: 99%
“…Glycosidase activity, phagosomal pH and proteolysis activity, and phagosomes purification Glycosidase activities in cell pellets and extracellular fluid were assessed as previously described (Froquet et al, 2008;Le Coadic et al, 2013). For phagosomal pH measurement, 3-µm carboxylated silica beads coupled to the pH-sensitive fluorophore FITC and to the pH-insensitive fluorophore Alexa-Fluor-594 were used.…”
Section: Plasmids Cell Transfections and Knockout Strainsmentioning
confidence: 99%
“…They are found in the endosomal compartments of yeast, Dictyostelium and human cells where they possibly contribute to cell migration, vesicular transport, endocytic trafficking and autophagy [11,12,17,18,19,20,21]. In Dictyostelium, TM9SF4/Phg1A is required for the phagocytosis and killing of bacteria [16,22,23]. Moreover, the two Dictyostelium TM9 proteins Phg1A and Phg1B synergistically contribute to the expression and/or localization of transmembrane proteins [14,24].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, only the mature form of cathepsin D was detected in WT and acapA 2 cells (data not shown), suggesting that there was normal maturation of lysosomal enzymes in the absence of ACAP-A. Next, we measured the proteolytic activity of phagosomes in living cells using beads coupled to Alexa Fluor 594 and to BSA labeled with DQ-Green at a self-quenching concentration, which become dequenched upon proteolysis of BSA Le Coadic et al, 2013). We observed that protease activity was substantially increased in acapA 2 cells (Fig.…”
Section: Fluid-phase Endocytic Defects In the Absence Of Acap-amentioning
confidence: 99%
“…After 4 h at 22˚C, migration distances were calculated by measuring displacement of cell front. Glycosidase activities (N-acetyl bglucosaminidase and a-mannosidase) and cathepsin D content in cell pellet and culture medium after 3 days of culture were assessed as previously described (Froquet et al, 2008;Le Coadic et al, 2013). For enzymatic activities and western immunoblot analysis, equal amounts of protein were analyzed.…”
Section: Antibodies and Immunofluorescence Microscopymentioning
confidence: 99%
See 1 more Smart Citation